Pipeline leak detection handbook - Henrie, Morgan; Carpenter, Philip; Nicholas, R. Edward (Gulf Professional Publishing is an imprint of Elsevier, 2016)
Pipeline Leak Detection Handbook is a concise, detailed, and inclusive leak detection best practices text and reference book. It begins with the basics of leak detection technologies that include leak detection systems, and information on pipeline leaks, their causes, and subsequent consequences. The book moves on to further explore system infrastructures, performance, human factors, installation, and integrity management, and is a must-have resource to help oil and gas professionals gain a comprehensive understanding of the identification, selection, design, testing, and implantation of a leak detection system.